Administration in Theological Libraries - Keck, Andrew (The Theological Librarian's Handbook, 2021)
Models for the administration of theological libraries vary significantly based on size, location, culture, and context. Commonly, theological libraries must develop an internal administration of policies, procedures, and goals in relation to collection management, staffing/volunteers, planning, reporting, and budget, as well as administer external relationships to a broader institution, library consortia, and other stakeholders. The targeted audience for this volume includes those starting a new theology library or beginning a new position in administration with principles relevant to established libraries and library directors.